Daphnetin Attenuated Cisplatin-Induced Acute Nephrotoxicity With Enhancing Antitumor Activity of Cisplatin by Upregulating SIRT1/SIRT6-Nrf2 Pathway - Fan, Xiaoye; Wei, Wei; Huang, Jingbo; Peng, Liping; Ci, Xinxin (Frontiers in Pharmacology, 2020)
Cisplatin (CDDP) is a widely used drug for cancer treatment that exhibits major side effects in normal tissues, such as nephrotoxicity in kidneys. The Nrf2 signaling pathway, a regulator of mitochondrial dysfunction, oxidative stress and inflammation, is a potential therapeutic target in CDDP-induced nephrotoxicity. We explored the underlying mechanisms in wild-type (WT) and Nrf2-/- mice on CDDP-induced renal dysfunction in vivo. We found that Nrf2 deficiency aggravated CDDP-induced nephrotoxicity, and Daph treatment significantly ameliorated the renal injury characterized by biochemical markers in WT mice and reduced the CDDP-induced cell damage. In terms of the mechanism, Daph upregulated the SIRT1 and SIRT6 expression in vivo and in vitro. Furthermore, Daph inhibited the expression level of NOX4, whereas it activated Nrf2 translocation and antioxidant enzymes HO-1 and NQO1, and alleviated oxidative stress and mitochondrial dysfunction. Moreover, Daph suppressed CDDP-induced NF-κB and MAPK inflammation pathways, as well as p53 and cleaved caspase-3 apoptosis pathways. Notably, the protective effects of Daph in WT mice were completely abrogated in Nrf2-/- mice. Moreover, Daph enhanced, rather than attenuated, the tumoricidal effect of CDDP.